Non-parametric tests of productive efficiency with errors-in-variables - Kuosmanen, Timo; Post, Thierry; Scholtes, Stefan (Elsevier, 2007)
We develop a non-parametric test of productive efficiency that accounts for errors-in-variables, following the approach of Varian. [1985. Nonparametric analysis of optimizing behavior with measurement error. Journal of Econometrics 30(1/2), 445-458]. The test is based on the general Pareto-Koopmans notion of efficiency, and does not require price data. Statistical inference is based on the sampling distribution of the L8 norm of errors. The test statistic can be computed using a simple enumeration algorithm. The finite sample properties of the test are analyzed by means of a Monte Carlo simulation using real-world data of large EU commercial banks.
Keywords: tehokkuus; tuottavuus; testit; menetelmät; non-parametric production analysis; data envelopment analysis; errors-in-variables